Evaluation of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - Anderson, S.; Khan, F.; Robledo, C.; Roth, C. (CGIAR Independent Evaluation Arrangement, 2016)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) aims to address the increasing challenge of global warming and declining food security on agricultural practices, policies and measures. The program is implemented in strategic collaboration between CGIAR and Future Earth, which is the umbrella organisation established to lead global science initiatives on planetary change, including climate modelling, land cover change, earth system governance and greenhouse gas emissions. The CCAFS goal is to promote a food‐secure world through the provision of science‐based efforts that support sustainable agriculture and enhance livelihoods while adapting to climate change and conserving natural resources and environmental services. In its theory of change emphasis is put on strategic partnerships, capacity building, communication, open access data, real time monitoring and evaluation and a strong focus on gender. The primary purpose of this evaluation is to enhance the contribution that CCAFS is likely to make towards reaching the CGIAR goals and towards reducing poverty and improving food security for people whose livelihoods depend on aquatic agricultural systems. As for all CRP evaluations, the purpose of the evaluation is to provide essential evaluative information for decision-making by Program management and its funders on issues such as extension, expansion and structuring of the program and adjustments in some aspects of the program. The Evaluation Team leader is Simon Anderson supported by a team of specialists. IEA Evaluation Manager for CCAFS is Sirkka Immonen supported by Sophie Zimm.